A role for the BDNF gene Val66Met polymorphism in schizophrenia? A comprehensive review. (April 2015) - Notaras, Michael; Hill, Rachel; van den Buuse, Maarten
Highlights: We comprehensively review the relevance of the Val66Met variant in schizophrenia. Other gene variants and environmental factors interact with Val66Met genotype. Val66Met variant modifies cognition and brain morphology in schizophrenia probands. Val66Met reduces age of onset and modifies the clinical phenotype of schizophrenia. Val66Met knock-in mice recapitulate endophenotypes of relevance to schizophrenia. Abstract: Schizophrenia is believed to arise from complex gene–environment interactions. Brain-derived neurotrophic factor (BDNF) is involved in neuronal development, differentiation and plasticity. A functional single nucleotide polymorphism that results in a valine (Val) to methionine (Met) substitution at codon 66 (Val66Met) results in the aberrant sorting and release of mature BDNF through the activity-dependent secretion pathway. The Val66Met polymorphism has been linked to impaired neurocognitive function in healthy adults, and identified as a locus of risk for a range of neuropsychiatric disorders including schizophrenia. Here we provide a comprehensive review of the relationship between the BDNF Val66Met polymorphism and schizophrenia, integrating evidence from the fields of genetic epidemiology, clinical psychiatry, behavioral neuroscience and neuroimaging. We argue that while the Val66Met polymorphism may not be a major risk-conferring agent for the development of schizophrenia per se, there is mounting evidence that the polymorphism modulates a range of clinical features of the illness, including age of onset, symptoms, therapeutic responsiveness, neurocognitive function and brain morphology.